Research progress on the prevention and treatment of hyperuricemia by medicinal and edible plants and its bioactive components - Cheng-yuan, Wang; Jian-gang, Dai (Frontiers in Nutrition, 2023)
Hyperuricemia is another common metabolic disease after “three high” and is considered to be closely related to the development of many chronic diseases. Currently, although the drugs show positive therapeutic effects, they have been shown to produce side effects that can be damaging to the body. There is growing evidence that medicinal and edible plants and its bioactive components have a significant effect on hyperuricemia. In this paper, we reviewed common medicinal and edible plants with uric acid-lowering effects and summarize the uric acid-lowering mechanisms of different bioactive components. Specifically, the bioactive components are divided into five categories, namely flavonoids, phenolic acids, alkaloids, polysaccharides and saponins. These active substances exhibit positive uric acid-lowering effects by inhibiting uric acid production, promoting uric acid excretion and improving inflammation. Overall, this review examined the potential role of medicinal and edible plants and its bioactive components as a means of combating hyperuricemia in the hope of providing some reference value for the treatment of hyperuricemia.